α-Stratified modules over the Lie algebra sl (n, ℂ) - Mazorchuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Properties of the generalized Weyl group are studied for α-stratified modules over the Lie algebra sl (n, ℂ).